What is the next structure? Guessing enhances L2 syntactic learning in a syntactic priming task - Alzahrani, Alaa (Frontiers in Psychology, 2023)
Previous psycholinguistic research has shown that Second Language (L2) speakers could learn from engaging in prediction. Few works have directly examined the relationship between prediction and L2 syntactic learning. Further, relatively limited attention has been paid to the effects of two linguistic factors in this area: structure type and L2 proficiency. Using a mixed experimental design, 147 L2 Arabic speakers with varying L2 proficiency levels completed two syntactic priming experiments, each targeting a different structure: (a) the dative and (b) Temporal Phrases (TP). The experimental conditions required participants to predict what the upcoming sentence’s structure would be. The experimental conditions differed in the degree of engagement in prediction error. Results suggested that Arabic L2 speakers at different proficiency levels showed enhanced priming and short-term learning for two syntactic structures (PO, fronted TP) when (a) instructed to guess only (constrained condition) as well as when (b) instructed to guess and compute the prediction error (unconstrained condition), relative to the controls. These results imply a guessing benefit for priming and short-term learning. Participants also experienced different priming effects by structure type, but there was no significant effect for proficiency. The theoretical and practical implications of these findings are discussed.